Change in physical activity level and clinical outcomes in older adults with knee pain: a secondary analysis from a randomised controlled trial - Quicke, Jonathan G.; Foster, Nadine E.; Croft, Peter R.; Ogollah, Reuben O.; Holden, Melanie A. (BioMed Central, 2018)
BACKGROUND: Exercise interventions improve clinical outcomes of pain and function in adults with knee pain due to osteoarthritis and higher levels of physical activity are associated with lower severity of pain and higher levels of physical functioning in older adults with knee osteoarthritis in cross-sectional studies. However, to date no studies have investigated if change in physical activity level during exercise interventions can explain clinical outcomes of pain and function. This study aimed to investigate if change in physical activity during exercise interventions is associated with future pain and physical function in older adults with knee pain.